Nonlinear Optical Response of Smectic Glasses Based on Cobalt Alkanoates - Gridyakina, A.V.; Garbovskiy, Yu.A.; Klimusheva, G.V.; Polischuk, A.P. (Ukrainian Journal of Physics, 2012)
The nonlinear-optical response of anisotropic smectic glasses based on cobalt-alkanoates is studied using the method of dynamic holography. Laser-induced dynamic gratings under the action of nanosecond laser pulses are observed and analyzed for such materials. It is found that a cubic optical nonlinearity of all studied anisotropic glasses is of electronic origin in the nanosecond diapason and caused by a nonlinear polarization of cobalt-alkanoates complexes.